Arts & crafts - Robinson, Michael (The world's greatest art, 2018)
"Arts & Crafts takes a look at this far-reaching and influential design movement. Covering furniture, decorative arts and architecture, the Arts and Crafts movement was to have a profound effect in the interior design of homes throughout Europe, America, Scandinavia and Japan, an effect that is still continuing today. The Arts and Crafts movement began in the late nineteenth-century Britain. as a reaction against the mass-produced furniture and textiles that had been made possible due to new industrial capabilities. William Morrison, John Ruskin, Philip Webb Walter Crane and others passionately believed that the status of decorative arts should be elevated to that of fine arts, and to do so meant that a return to good craftsmanship and design was essential. This book follows the development of the Arts and Crafts movement through the artifacts and designs that were produced at the time, providing a fascinating glimpse into a design movement that celebrated a return to simplicity and individual creativity.--"